(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Information regarding this paper discusses the review of Repair and Maintenance of Industrial building. In the current scenario of industrial building research, repair and maintenance place a vital role as it serves important in industrial building. Industrial building and other structure have a certain useful life. In industrial building various defects are generated due to different causes e.g. in some cases defects are caused after the structure has been complete for the few years which results in shortening of life and strength of structure. We have visited and study the various defects occurred in “AAKAR MDS” at Bhosari which is located at district Pune, state Maharashtra, India. Aim of the paper is to conduct literature review of different approaches to defining the building maintenance and repair. The major defects reported are discussed and suitable and economical solution for the particular defects is identify by a tradeoff between cost, lifetime, and adaptability of the solution.